Patterns of relapse in glioblastoma multiforme following concomitant chemoradiotherapy with temozolomide. - Sherriff, J; Tamangani, J; Senthil, L; Cruickshank, G; Spooner, D; Jones, B; Brookes, C; Sanghera, P (2013)
OBJECTIVE: Different methods for contouring target volumes are currently in use in the UK when irradiating glioblastomas post operatively. Both one- and two-phase techniques are offered at different centres. 90% of relapses are recognised to occur locally when using radiotherapy alone. The objective of this evaluation was to determine the pattern of relapse following concomitant radiotherapy with temozolomide (RT-TMZ). METHODS: A retrospective analysis of patients receiving RT-TMZ between 2006 and 2010 was performed. Outcome data including survival were calculated from the start of radiotherapy. Analysis of available serial cross-sectional imaging was performed from diagnosis to first relapse. The site of first relapse was defined by the relationship to primary disease. Central relapse was defined as progression of the primary enhancing mass or the appearance of a new enhancing nodule within 2 cm. RESULTS: 105 patients were identified as receiving RT-TMZ. 34 patients were not eligible for relapse analysis owing to either lack of progression or unsuitable imaging. Patterns of first relapse were as follows: 55 (77%) patients relapsed centrally within 2 cm of the original gadolinium-enhanced mass on MRI, 13 (18%) patients relapsed >4 cm from the original enhancement and 3 (4%) relapsed within the contralateral hemisphere. CONCLUSION: Central relapse remains the predominant pattern of failure following RT-TMZ. Single-phase conformal radiotherapy using a 2-cm margin from the original contrast-enhanced mass is appropriate for the majority of these patients. ADVANCES IN KNOWLEDGE: Central relapse remains the predominant pattern of failure following chemoradiotherapy for glioblastomas.